Derivatives trading and volatility spill-over: evidence from a developing derivatives market - Muhammad, Junaina; Amin Noordin, Bany Ariffin; Yahya, Mohamed Hisham (Universiti Putra Malaysia Press, 2013)
The objective of the paper is to ascertain the influence of shares derivatives trading on the Malaysian stock market. Johansen-Juselius’ co-integration test reveals signs of increasing integration between these cash and futures markets over time. The Granger causality test indicates that the stock index futures Granger causes the cash index with no feedback in the reverse direction during periods of financial crisis and recovery. Significantly observable during the period was high participation of foreign investors in the futures market. The increase in the number of foreign investors in the futures market dramatically increases the herding activities in futures market trading. The findings suggest that the transmission of information from the futures market to the cash market could, to a certain extent, during a period of “bad economy”, be due to herding by foreign investors.